2023
DOI: 10.1021/acsaem.3c00969
|View full text |Cite
|
Sign up to set email alerts
|

Polyimides as Promising Cathodes for Metal–Organic Batteries: A Comparison between Divalent (Ca2+, Mg2+) and Monovalent (Li+, Na+) Cations

Abstract: Ca-and Mg-based batteries represent a more sustainable alternative to Liion batteries. However, multivalent cation technologies suffer from poor cation mass transport. In addition, the development of positive electrodes enabling reversible charge storage currently represents one of the major challenges. Organic positive electrodes, in addition to being the most sustainable and potentially low-cost candidates, compared with their inorganic counterparts, currently present the best electrochemical performances in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, bulk organic electrodes are known to exhibit diffusion-controlled redox processes, which suffer from poor rate and cycling performance. [57] At potentials above −0.1 V versus Ag/AgCl, both Ti 3 C 2 T x and Ti 3 C 2 T x @cPDI exhibit double-layer charging, giving rise to intercalation capacitance. The representative cyclic voltammograms from 5 to 100 mV s −1 are shown in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…However, bulk organic electrodes are known to exhibit diffusion-controlled redox processes, which suffer from poor rate and cycling performance. [57] At potentials above −0.1 V versus Ag/AgCl, both Ti 3 C 2 T x and Ti 3 C 2 T x @cPDI exhibit double-layer charging, giving rise to intercalation capacitance. The representative cyclic voltammograms from 5 to 100 mV s −1 are shown in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…Redox polymers are also known for the versatility of their redox chemistry and the possibility of using different ions from Li and Na including multivalent ions such as Mg, Ca, or Al to organics. For instance, several redox polymers including catechol, polyimides, or phenothiazine have recently been demonstrated as universal hosts for aqueous rechargeable batteries based on mono-, di-, or trivalent cations. As two seminal examples of the possibilities of using multivalent ions, an ultrahigh performance zinc–organic battery using a poly­(catechol) cathode in concentrated aqueous electrolytes was recently shown by Marcilla and co-workers, and Esser et al demonstrated recently an aluminum–organic battery …”
Section: Polymers As Separator Electrolytementioning
confidence: 99%
“…To meet society’s growing needs for renewable energy storage, novel battery chemistries with higher energy density and lower cost than Li-ion batteries need to be developed. , Ca metal batteries have been proposed as alternatives to Li-ion batteries due to the greater crustal abundance (41,500 mg/kg for Ca vs 20 mg/kg for Li) and anode capacity (1337 mAh/g for Ca metal anodes vs 372 mAh/g for Li/C 6 anodes). Despite these advantages, development of Ca metal batteries has been limited. , …”
Section: Introductionmentioning
confidence: 99%